La mejora ambiental manifiestamente evidente: mirada optimista a una figura actualmente poco amigable - Ruesta Otoya, Favio (Pontificia Universidad Católica del Perú, 2022)
In 2013, the Agency for Environmental Assessment and Enforcement introduced the manifestly evident environmental improvement to the legal system. This figure had a negative reception as it seemed to delegitimize the obligations established in the environmental certification, the most important environmental license in Peru.This paper analyses the questions born with the creation of the manifestly evident environmental improvement and the effective use of this figure by the public.

En 2013, el Organismo de Evaluación y Fiscalización Ambiental introdujo al ordenamiento jurídica la mejora ambiental manifiestamente evidente. Dicha figura tuvo una recepción negativa pues parecía deslegitimar las obligaciones establecidas en la certificación ambiental, la licencia ambiental más importante en el Perú.En este trabajo se analizan las incógnitas nacidas con la creación de la mejora ambiental manifiestamente evidente y la utilización efectiva de esta figura por parte de los administrados.
The manifestly evident environmental improvement: optimistic look at a figure that is currently unfriendly
Keywords: Environmental improvement to the legal system; Environmental certification; Environmental license; OEFA; Peru; Mejora ambiental manifiestamente evidente; Certificación ambiental; OEFA; Perú; https://purl.org/pe-repo/ocde/ford#5.05.01